Redescription of two species of freshwater crabs from Tanzania, East Africa: Arcopotamonautes unisulcatus (Rathbun, 1933) and A. xiphoidus (Reed & Cumberlidge, 2006) (Brachyura: Potamoidea: Potamonautidae) - Cumberlidge, Neil; Huiskens, Alyssa J.; Jonas, Gabrielle I. (Zootaxa, 2025)
This work focuses on two little-known species of freshwater crabs from Tanzania, East Africa: Arcopotamonautes unisulcatus (Rathbun, 1933) and A. xiphoidus (Reed & Cumberlidge, 2006) (Potamoidea: Potamonautidae). Both species are redescribed in detail from the examination of type specimens and other available material, supported by diagnoses, illustrations, and a distribution map.